Mitigasi Relawan Muda Tangguh Bencana - Laily, Nur Vita; Ardani, Shinta Widia; Permadi, Andhy; Mubarok, Ahmad Sofiyyul (LPPM Universitas Bumigora, 2024)
Bajulan Village is a disaster-prone village which has experienced several disasters such as flash floods in 2020, fires in 2021, and landslides in 2021, 2022, 2023. This service aims to build a community of young Bajulan volunteers who are able to help other communities in dealing with all disasters, especially landslides. Not only that, this service also aims to install disaster signs to provide information to the community about which areas have a higher risk of landslides. The methodology used is Participatory Action Research. This method is used because it makes the community play an active role as the main actor in solving problems and researchers only act as facilitators. Then this method is used to get maximum results. In this method there is also an important stage called Focus Group Discussion which is a forum for residents to voice what their problems are and how residents can overcome them. Researchers invited the Regional Disaster Management Agency as a speaker on disaster mitigation education in the discussion. The result of this service is data that shows the main causes of landslides. Then, data shows how residents deal with landslides. Another result is the formation of a community of young volunteers for disaster resilience and disaster signs.